Endoscopic dilatation of piloric strictures as a sequela - de Simone, Gustavo; Zimmer, Walter; Sojo, Enrique (Cirugía del Uruguay, 1981)
Gastroduodenal fibroscopy has shown that the healing of piloric, antral and duodenal ulcers in the vicinity of the pilorus gives rise to deformities or strictures that al'ter normal gastric evacuation.